The Blackwell encyclopedia of modern Christian thought - McGrath, Alister Edgar, 1953- (Oxford, UK Blackwell, 1993)
Includes bibliographical references and index.
Keywords: Theology -- 17th century -- encyclopedias; Theology -- 19th century -- encyclopedias; Theology -- 20th century -- encyclopedias; Theologians -- biography -- encyclopedias